2021
DOI: 10.3390/molecules26061544
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Extracellular Vesicles Based Drug Delivery Systems

Abstract: Extracellular vesicles (EVs) play major roles in intracellular communication and participate in several biological functions in both normal and pathological conditions. Surface modification of EVs via various ligands, such as proteins, peptides, or aptamers, offers great potential as a means to achieve targeted delivery of therapeutic cargo, i.e., in drug delivery systems (DDS). This review summarizes recent studies pertaining to the development of EV-based DDS and its advantages compared to conventional nano … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 156 publications
(172 reference statements)
0
41
0
Order By: Relevance
“…At present, EVs receive special attention as physiological delivery tools, the usage of which reduces the side effects of treatment. However, the latter application is still fraught with many challenges, including enhancing their biological effectiveness and directing them towards desired target cells [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, EVs receive special attention as physiological delivery tools, the usage of which reduces the side effects of treatment. However, the latter application is still fraught with many challenges, including enhancing their biological effectiveness and directing them towards desired target cells [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, EVs have emerged as a promising NDS with huge application in cancer therapy as well as diagnosis. A detailed review of the factors reacting with EV-based drug delivery systems has been reported by our group previously [151]. Interestingly, the surface modification of EVs has a great potential to achieve the targeting ability [152].…”
Section: Conjugation Of Peptides and Extracellular Vesicles (Cpevs) For Cancer Therapymentioning
confidence: 95%
“…Recently, several studies have proposed the use of exosomes as potential DDSs for therapeutic application in cancer to overcome the problems associated with synthetic DDSs. These EVs serve as efficient vehicles for tumor-targeted delivery because their biological origin reduces the immune response, they can cross biological barriers including the blood brain barrier (BBB) [ [165] , [166] , [167] , [168] ], and can transfer their cargo to nearby or distant cells. In addition there are adhesion proteins on their surface, and they are small in size with excellent stability, biocompatibility and safety [ 156 , 161 , 162 , 169 ].…”
Section: Exosome-based Delivery Systems For Cancer Therapeuticsmentioning
confidence: 99%